جهود المختصرات التفسيرية في تقرير قواعد الربوبية: تفسير الجلالين أنموذجا: The Role of Tafsir Mukhtasar Scholars in Interpreting Rububiyyah Rules: A Study of the Book of Tafsir al-Jalālain - Tali, Hamza (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
At the basic level in various fields of science, it generally describes the completion of the building stages of these sciences and reaching the stage of maturity. At this stage, the desired fruit of these sciences can be grasped, and this stage also provides the foundations for the scientific tools needed to achieve scientific mastery. There is no doubt that the first thing researchers want to explain is the science of faith, because it is an urgent need for Muslims. Therefore, researchers are trying to achieve this noble goal by asking for help from Allah SWT. And the first source of Muslim faith is the Koran. Specifically, the study used the book of Tafsir al-Jalālain because of its popularity among Muslims, which was written to make it easier to read the Koran. This research will clearly explore the signs for establishing the rules of Rububiyyah monotheism in the book Tafsīr al-Jalālain. There is no doubt that attention to faith is not limited to tafsir books, which have extensive and detailed discussions, but concise tafsir books compete in discussing this aspect of the rububiyyah. Through this research, it is also confirmed that paying attention to the rububiyyah aspect is an important stage for the basic foundations in general, both with the preaching community and the ijabah community. What encourages researchers to pay attention to this important aspect of the faith is serving the Islamic faith and providing enlightenment to Muslims.